Relationship between VacA Toxin and Host Cell Autophagy in Helicobacter pylori Infection of the Human Stomach: A Few Answers, Many Questions - Ricci, Vittorio (Toxins (Basel), 2016)
Helicobacter pylori is a Gram-negative bacterium that colonizes the stomach of about half the global population and represents the greatest risk factor for gastric malignancy. The relevance of H. pylori for gastric cancer development is equivalent to that of tobacco smoking for lung cancer. VacA toxin seems to play a pivotal role in the overall strategy of H. pylori towards achieving persistent gastric colonization. This strategy appears to involve the modulation of host cell autophagy. After an overview of autophagy and its role in infection and carcinogenesis, I critically review current knowledge about the action of VacA on host cell autophagy during H. pylori infection of the human stomach. Although VacA is a key player in modulation of H. pylori-induced autophagy, a few discrepancies in the data are also evident and many questions remain to be answered. We are thus still far from a definitive understanding of the molecular mechanisms through which VacA affects autophagy and the consequences of this toxin action on the overall pathogenic activity of H. pylori.